Pengaruh Media Sosial terhadap Pola Interaksi Kelompok Masyarakat - Aritonang, Adelina M.; Pasaribu, Ertika Susanti; Purba, Herlide; Siburian, Pebryna Riosa; Yunita, Sri (Lembaga Intelektual Muda (LIM) Maluku, 2024)
The use of social media has become an integral part of the lives of modern societies, significantly changing the way individuals and groups interact. Social media improves connectivity and access to information, facilitates the formation of virtual communities, and expands social networks. However, these changes also have negative impacts, such as disruption of face-to-face interaction and polarization in community groups. The type of research used is qualitative research using the literature study method or literature can be interpreted as a series of activities related to the method of collecting library data, reading and recording and processing research materials that use books, journals and other literature as the main object. The main source of this research data is research articles published in the last 10 years through the google scholar website. Data analysis was carried out qualitatively consisting of data reduction, data presentation, and conclusion drawn. The results show that social media provides convenience in interacting and accessing information, but also poses challenges such as polarization, inaccurate information dissemination, and disruption in face-to-face interactions.